Successful Treatment of Cerebral Toxoplasmosis Using Pyrimethamine Oral Solution Compounded From Inexpensive Bulk Powder. (18th April 2018) - Hodgson, Hayley A; Sim, Taeyong; Gonzalez, Hemil; Aziz, Mariam; Rhee, Yoona; Lewis, Paul O; Jhobalia, Neel; Shields, Beth; Wang, Sheila K
Abstract: A price increase of pyrimethamine tablets in the United States has made the life-saving drug difficult to acquire for hospitalized patients who need it most. We report the successful use of a pyrimethamine oral suspension compounded from an economical bulk powder in a patient with acute toxoplasmic encephalitis.